Eggs - Roux, Michel (London, United Kingdom : Quadrille Publishing Limited, 2005)
"Destined to become a staple on the bookshelves of everyone who likes to cook and illustrated throughout with stunning photographs by award-winning photographer Martin Brigdale, 'Eggs' is a compilation of Roux's 100 best egg recipes."
Boiled & mollet eggs -- Poached eggs -- Fried eggs -- Scrambled eggs -- Baked eggs -- Omelettes -- Souffles -- Crepes & batters -- Egg-rich pastries & pasta -- Custards, creams & mousses -- Ice creams -- Meringues & sponges -- Sauces & dressings.
Includes index.
Keywords: COOKING -- EGGS